Metropolitan Business Association of Chicago contingent - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two men holding a banner that reads, "Metropolitan Business Association of Chicago". Other men march behind the banner as they participate in the National March on Washington for Lesbian and Gay Rights.